Item parameters of Yureka Education Center (YEC) English Proficiency Online Test (EPOT) instrument - Endrati Jati Siwi; Rosyita Anindyarini; Sabiqun Nahar (Universitas Negeri Yogyakarta, 2020)
Yureka Education Center (YEC) is one of the institutions which has developed an online-based English proficiency test. The test is called the English Proficiency Online Test (EPOT) which follows the TOEFL ITP (Institutional Testing Program) framework. Thus, this study aimed to analyze the characteristics of EPOT instruments consisting of Listening, Structure, and Reading subtests, which later the quality of each EPOT test item is identified. This study used a descriptive quantitative approach by describing the characteristics of EPOT test items in terms of item difficulty index, item discrimination index, test information's function, and test measurement's errors. The data were collected through EPOT trials conducted by 2,652 online test-takers as participants from 20 provinces in Indonesia. The collected data were then analyzed using the Item Response Theory (IRT) approach using the BILOG program on all logistic parameter models which began with the item compatibility test against the model. Based on the results of the analysis, all subtests match the 3-PL model. Most of EPOT's test items had a good range of difficulty index and discrimination index. The EPOT information's function shows that accurate items are used on the 3-PL model for a certain capability range. This study is expected to point out that the EPOT test could be used as an alternative English proficiency test that is easy to use and useful.